PERSEPSI MASYARAKAT TERHADAP WISATA HUTAN MANGROVE DI DESA BUDO KECAMATAN WORI KABUPATEN MINAHASA UTARA - Demotekay, Philips Gabriel; Pakasi, Caroline Betsi Diana; Tangkere, Ellen Grace (AGRI-SOSIOEKONOMI, 2022)
This study aims to determine and analyze public perceptions of the development of mangrove tourism in Budo Village, Wori District, North Minahasa Regency. The research was carried out from September to November 2021. The data used came from primary data and secondary data and then analyzed descriptively. Sampling was determined intentionally or purposive sampling, with the number of respondents taken as many as 20 people. The data analysis used in this research is descriptive data analysis using Likert scale measurement using data tables and numbers. The results showed that the community's perception of mangrove forest tourism in Budo Village had a very good category because the community strongly agreed with the government program in the aspect of mangrove management as well as the utilization of mangrove resources and protection of the Mangrove Forest and in addition through the Village-Owned Enterprises (BUMDES). Mangrove forest is used as a tourist attraction that brings benefits to the community so that it can generate income and become jobs for the community in Budo Village.